Cephalometry Variation of Bataknese - Maria Natalina Lumban Gaol; Niken Satuti Nur Handayani (Berkala Ilmiah Biologi, 2022)
Indonesia is a country that consists of various ethnic groups, one of the largest ethnic groups in Indonesia is Bataknese. Bataknese divided into several sub-ethnics, with the largest sub-ethnics are Batak Toba, Batak Karo and Batak Simalungun. This research aims to analyze cephalometric variation of Bataknese. An increase of various ethnic groups in various regions, followed by an increase in traffic activity and the quantity of crime can lead to an increase of traffic accidents and crime victims. Therefore, this research needs to be carried out to determine cephalometric variations and cephalometric index in the Bataknese which can be used in the process of revealing the identity of crime victims and traffic accidents. This research involved 60 subjects of Bataknese, consisting of 20 people of Batak Toba, 20 people of Batak Karo, and 20 people of Batak Simalungun. The method in this research consisted of submit ethical clearance, subject data collection, subject measurement, cephalometric index calculation, and data analysis. The results showed that Batak Toba, Karo, and Simalungun have brachycephalic head type, wide forehead type, and platyrrhine nose type. Batak Toba and Batak Karo are known to have a leptoprosopic facial type, while Batak Simalungun has mesoprosopic facial type. In this research, it was also showed that between Batak Toba and Batak Karo there were no significant differences in all body size and cephalometric data, but between Batak Toba and Batak Simalungun there were significant differences in minimum frontal width, nose width, and frontoparietal index, while between Batak Simalungun and Batak Karo there were significant differences in minimum frontal width and facial width.